2013
DOI: 10.1186/2047-783x-18-30
|View full text |Cite
|
Sign up to set email alerts
|

Visualisation of the Bonebridge by means of CT and CBCT

Abstract: BackgroundWith the Bonebridge, a new bone-anchored hearing aid has been available since March 2012. The objective of the study was to analyse the visualisation of the implant itself as well as its impact on the representation of the bony structures of the petrosal bone in CT, MRI and cone beam CT (CBCT).MethodsThe Bonebridge was implanted unilaterally in two completely prepared human heads. The radiological imaging by means of CBCT, 64-slice CT, 1.5-T and 3.0-T MRI was conducted both preoperatively and postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
0
15
0
3
Order By: Relevance
“…With dedicated software, the positioning of the BC-FMT can be planned in order to avoid any compression of the sinus and dura, and to locate the screws on the same plane [6,7]. In case of atresia auris, where a pinna reconstruction is planned at a later stage, the incision should be done further posteriorly [8.…”
Section: Introductionmentioning
confidence: 99%
“…With dedicated software, the positioning of the BC-FMT can be planned in order to avoid any compression of the sinus and dura, and to locate the screws on the same plane [6,7]. In case of atresia auris, where a pinna reconstruction is planned at a later stage, the incision should be done further posteriorly [8.…”
Section: Introductionmentioning
confidence: 99%
“…Posztoperatív utánkövetés is alacsony sugárdózissal biztosítható CBCT-vel. Középfül-implantátum beülteté-sét követő vizsgálatok során a CBCT jobbnak bizonyult a multislice CT-vel összehasonlítva a képminőség tekintetében, mivel kevesebb műtermék keletkezik [20]. Cochlearis implantáció a csökkent fém műtermék miatt megbízhatóbban kontrollálható CBCT-vel [5].…”
Section: Fülészeti Implantátumokunclassified
“…To the best of the authors' knowledge, there are no reported studies on either CBCT or CT on flat hearing implants, where the transducer is in contact with bone. A recent human cadaver study [Guldner et al, 2013] concluded that a similar hearing implant, the Bonebridge TM (Med-El, Innsbruck, Austria), and surrounding anatomical structures could be visualized using CT and CBCT, where CBCT had an advantage in image quality. The flat medial surface of the Bonebridge transducer is, however, not in contact with bone.…”
Section: Cbct and Ctmentioning
confidence: 99%